Seasonal and interannual variations of gravity wave activity in the low-latitude mesosphere and lower thermosphere over Tirunelveli (8.7° N, 77.8° E) - Sridharan, S.; Sathishkumar, S. (My University, 2008)
The Mesosphere and Lower Thermosphere (MLT) winds acquired by medium frequency (MF) radar at Tirunelveli (8.7° N, 77.8° E) for the years 1993–2007 are used to study seasonal and interannual variabilities of gravity wave (GW) variances in the altitude region 84–94 km. The GW variances in zonal and meridional winds show semiannual oscillation with maximum variance during March–April and August–September and minimum during June–July and November–December months. The wind variances, in general, are observed to be enhanced during and after the year 1998 and they undergo large interannual variability, in particular, during spring equinox months. An enhancement of GW variances is observed during spring equinox months of the years 2000, 2004 and 2006. These larger GW enhancements, most of the times, coincide with eastward phase of zonally averaged stratospheric QBO at 30 hPa over equator and sudden stratospheric warming occurred at high latitudes. From the zonal and meridional variances, the perturbation ellipses are calculated and they show that the predominant direction of propagation of gravity waves is in SE-NW plane.
Keywords: Gravity waves; Low-latitude mesosphere; Thermosphere; Waves and tides; MLT winds